Deletion of Chromosome 4q Predicts Outcome in Stage II Colon Cancer Patients. (2010) - Brosens, R. P. M.; Belt, E. J. T. H.; Haan, J. C.; Buffart, T. E.; Carvalho, B.; Grabsch, H.; Quirke, P.; Cuesta, M. A.; Engel, A. F.; Ylstra, B.; Meijer, G. A.
Abstract : Background : Around 30% of all stage II colon cancer patients will relapse and die of their disease. At present no objective parameters to identify high-risk stage II colon cancer patients, who will benefit from adjuvant chemotherapy, have been established. With traditional histopathological features definition of high-risk stage II colon cancer patients is inaccurate. Therefore more objective and robust markers for prediction of relapse are needed. DNA copy number aberrations have proven to be robust prognostic markers, but have not yet been investigated for this specific group of patients. The aim of the present study was to identify chromosomal aberrations that can predict relapse of tumor in patients with stage II colon cancer. Materials and Methods : DNA was isolated from 40 formaldehyde fixed paraffin embedded stage II colon cancer samples with extensive clinicopathological data. Samples were hybridized using Comparative Genomic Hybridization (CGH) arrays to determine DNA copy number changes and microsatellite stability was determined by PCR. To analyze differences between stage II colon cancer patients with and without relapse of tumor a Wilcoxon rank-sum test was implemented with multiple testing correction. Results : Stage II colon cancers of patients who had relapse of disease showed significantly more losses on chromosomes 4, 5, 15q, 17q and 18q. In the microsatellite stable (MSS) subgroup ( n =28), only loss of chromosome 4q22.1–4q35.2 was significantly associated with disease relapse (p < 0.05, FDR < 0.15). No differences in clinicopathological characteristics between patients with and without relapse were observed. Conclusion : In the present series of MSS stage II colon cancer patients losses on 4q22.1–4q35.2 were associated with worse outcome and these genomic alterations may aid in selecting patients for adjuvant therapy.